Synthesis of visible light driven TiO2 coated carbon nanospheres for degradation of dyes - Waseem Raza; M.M. Haque; M. Muneer; D. Bahnemann (Arabian Journal of Chemistry, 2019)
Herein, we report the successful synthesis of visible light driven metal doped TiO2 coated carbon nanospheres (CNS) via a facile hydrothermal approach. The synthesized materials were characterized by standard analytical techniques, such as XRD, SEM–EDS-mapping, TEM, FTIR, PL, Raman and UV–Vis absorption spectroscopy. The effect of dopants on the band gap energy, crystallite size and photocatalytic properties of the TiO2 coated CNS was investigated systematically. The incorporation of dopants in TiO2 matrix found to significantly extend the absorption edge toward visible region and efficient separation of charge carriers on excitation. The photodegradation of two different organic dyes were investigated to evaluate the activity of the photocatalyst under different conditions such as dopant percentage, catalyst dose, different quenchers and calcination temperature. The best photocatalytic activity was observed with 3.0% Ce, doped TiO2 coated CNS with 1.5 g L−1 concentration calcined at 400 °C. We also performed the antibacterial activity of pure and doped-TiO2 coated CNS against pathogenic gram negative and gram positive bacteria. The doped-TiO2 coated CNS exhibited excellent antibacterial activity against both bacteria. Keywords: Metal doped TiO2, CNS coated TiO2, Photocatalysis, Dye degradation